POLITICAL POLARIZATION IN THE 2024 LOCAL ELECTIONS: AN ANALYSIS OF ITS IMPACT AND IMPLICATIONS FOR LOCAL DEMOCRACY IN INDONESIA - Muhtar, Muhtar; Setiyono, Budi; Fitriyah, Fitriyah; Sardini, Nur Hidayat (JWP (Jurnal Wacana Politik), 2025)
Regional head elections (Pilkada) are a crucial moment in Indonesia’s political dynamics, but in 2024, political polarization reached its peak, causing significant impacts on local democracy. This study aims to investigate the phenomenon of political polarization in the 2024 regional elections and analyze its implications for the sustainability of local democracy in Indonesia. Through a mixed approach that combines qualitative and quantitative analysis, this study attempts to understand the root causes of political polarization, measure the level of polarization in different regions, and evaluate the resulting political consequences. Political polarization in the context of the 2024 regional elections reflects the increasing tension between different political parties, especially in terms of ideological conflicts and differences in political views. It is influenced by factors such as national polarization, local political dynamics, and the increased use of social media as a tool to amplify divisive political narratives. The results show that political polarization in the 2024 local elections has far-reaching impacts on local democracy, including decreased public political participation, heightened political tensions, and the risk of social conflict that could potentially undermine political stability. The long-term implications of this political polarization highlight the need for appropriate measures to strengthen local democracy and rebuild public trust in the political process. In this context, efforts to promote inclusive political dialog, improve people’s political literacy, and reduce excessive political tension are crucial to maintaining the health of local democracy in Indonesia. Only with these measures can local democracy develop positively and embody strong and inclusive democratic principles amidst complex political dynamics.